Use of the Language Laboratory in the Communicative Methodology - Bambang Sugeng (TEFLIN, 1998)
<!– /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:none; text-autospace:none; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; mso-ansi-language:EN-US; mso-fareast-language:EN-US; @page Section1 size:612.0pt 792.0pt; margin:72.0pt 90.0pt 72.0pt 90.0pt; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> Abstract : The language laboratory has almost been forgotten lately partly due to intensive implementation of the communicative methodology in language teaching. This is unfortunate considering that, as a medium of instruction, the language laboratory is, like all other media, a means of reaching a goal. In this scheme, use of the language lab remains relevant. In order for the language lab to suit the communicative purposes certain requirements need to be fulfilled. First, since the goal of the communicative methodology is directed to communicative competence, the use of the language lab should be directed for this purpose. Second, a design should be attempted where use of the language laboratory will expose students with authentic language usc.Third, instructional strategics should be in concord with the comÃ¢â¬â municative principles such as communicative gaps, pre- and post-activities, and othcrs.Finally, lessons should be built integratively. Examples are given illustrating integration of the listening, speaking, reading, and writing skills in lesson units.